Establishment of bioenergy crops as a source of alternative energy, through the development of planting options in three sites in Costa Rica - Arnáez-Serrano, Elizabeth (2019)
In Costa Rica, an alternative to the use of fossil fuels is the use of plants with energetic potential; be this the direct biomass produced or the acquisition of fine oils. During the last eight years, a group of interdisciplinary researchers from the state universities of Costa Rica, have been conducting systematic studies on the cultivation of Jatropha curcas (Tempate) for commercial use as a source of oil to produce biodiesel; parallel since 2017 work with other species with bioenergy potential started, using castor bean (Ricinus comunis) and coyol (Acrocomia aculeata), among others. The research covers three objectives, first to establish crops of these species in different bioclimatic zones around the country, along with alternative systematic trials with (tempate, castor and coyol), in combination with food crops and animal feed. The second objective is focused on offering more productive and less toxic varieties of tempate (Jatropha curcas). And the last objective deals with technology and information transfer to the productive sector. The information obtained will allow new options to farmers and aid them to minimize the impact of climate change on their activities, as well as to contribute to the goals Costa Rica has proposed to reduce the emission and improve the quality of life of the Costa Rican population